Radiation and Emission Phenomena in Combination - Andrej Kuznetsov; Wisanu Pecharapa (My University, 2023)
Radiation and emission are often decoupled in applications, methods, or specific experiments. However, the principles of these phenomena are closely interconnected. It holds both to neighboring and relatively distant branches of science and technology, allowing for interesting synergies, while considering these phenomena in combination. For example, even though light emitting diodes and photovoltaic cells are two separate branches of modern science and technology, in foundation, both sectors rely on understanding of the principles of photon-matter interactions. Concurrently, in scientific methodologies, there are numerous examples for irradiation of samples with different types of particles (e.g., with ions, electrons, positrons, X-rays) and collecting the response of the interaction used to learn the properties. At no doubt, there are excellently working well-established narrow-focused conferences in the field, however organizing a broader scope conference reaching a high level of the professional quality is challenging. Indeed, there is a risk of defocusing and losing grounds for professional discussions as it often happens with emerging conferences around the globe trying to capitalize on the generic approaches, unfortunately with relatively limited success. On the contrary, as has been proven by its 5-year-long annual operation, the International Conference on Radiation and Emission in Materials (ICREM) is one of a few successful examples of such newly established events aiming to bring several research communities closer together. This success is exactly because of considering the radiation and emission phenomena in their natural combination, as such being paradoxically focused and generic at the same time. Notably, the next ICREM will take place in Chiang Mai during December 13–15, 2023 (https://www.icrem2023.com/), keeping a tradition of hosting ICREMs in Thailand. On this occasion, we are glad to invite researchers, industrialists, and students involved into all relevant fields to participate in ICREM2023, which will provide a great forum for knowledge-sharing, networking, and collaboration. The ICREM2022 (http://www.nano.kmitl.ac.th/icrem2021/) was the 4th edition of the ICREM. The event was affected by the restrictions related to the covid-2019 pandemic, forced to move the event from 2021 to spring 2022, even though the travelling barriers were still in place in spring 2022 in many countries unfortunately. The shift of the conference from 2021 to 2022 explains why one may see puzzling referencing to 2021 in the website. Nevertheless, the conference has attracted >120 participants and resulted in a strong collection of papers comprising the present physica status solidi (a) Special Issue. The papers gathered in this Special Issue may be categorized into three divisions: accelerated particle beams, advanced optical materials, and devices. Experiments and simulations with different sorts of energetic particles attracted significant attention at the ICREM2022. Specifically, Dauletbekova et al. (pssa.202200332) have revealed and reported the influence of neutron irradiation on the infrared absorption spectra of LiF crystals as a function of the contaminations, in particular with hydroxyl and metallic impurities. Thongbai et al. (pssa.202200398) have reported on an interesting development of the magnetic field measurement system as a part of the mid-infrared and terahertz radiation free-electron laser project at the Chiang Mai University in Thailand. Tang et al. (pssa.202200426) have reported on the most recent development at the pulsed muon facility (the so-called EMuS) at China Spallation Neutron Source (CSNS). Whitlow and Nagy (pssa.202200432) have used micro-particle induced x-ray emission to study the lead-free and lead-based solders as well as their interactions with copper wires. Yu (pssa.202200512) has reported on discoveries of the suppressed defect dynamics in SiO2-Si structures under high-to-low switched dose rate irradiations. Du et al. (pssa.202200515) have studied a phenomenon of lateral scattering of high energy heavy ions in solids applying a set of membranes as samples. Mastering of the light emission was among the major topic at the ICREM2022. Reshchikov (pssa.202200402) has provided a comprehensive review on photoluminescence bands occurring in gallium nitride and associated with point defects involving nitrogen or gallium vacancies. Jakrapong et al. (pssa.202200411) have reported on the significance of the X-ray luminescence, photoluminescence and radiation shielding properties of the Eu doped oxide glasses. Kiwsakunkran et al. (pssa.202200437) have studied photo and X-ray luminescence properties of complex glasses in particular demonstrating hypersensitive transitions at the visible and near infrared ranges, respectively. Yasaka et al. (pssa.202200438) have investigated optical properties of boro-tellurite glasses for photonic applications. Intachai et al. (pssa.202200440) have prepared Sm-doped gadolinium sodium silicoborate glasses by melt quenching process and investigated their luminescence properties suggesting feasibility for orange color emitting devices. Galeckas et al. (pssa.202200449) have reported the control of carrier lifetime on SiC films by thermal generation and annihilation of carbon vacancy, in particular using a combination of the luminescence-based depth-profiling, capacitance-voltage measurement and deep-level transient spectroscopy. Mishra et al. (pssa.202200466) have conducted cathodoluminescent imaging and secondary-ions mass spectrometry measurement on ZnO:N films under rapid thermal annealing process in N2 and O2 atmosphere and found an enhancement of acceptor-related cathodoluminescence in these films. Selim (pssa.202200712) has provided a review on advanced thermoluminescence spectroscopy, flagging it as a research tool to investigate crucial optical and electronic properties of semiconductor and photonic materials. Reports on devices for energy storage, radiation detection, photovoltaics, etc. comprised an integrated part of ICREM2022. In particular, Kornphom et al. (pssa.202200240) have reported improvements in the energy storage depending on the rhombohedral vs cubic phase balance in the samples. Thawong et al. (pssa.202200418) have demonstrated lead-free ceramics by solid-state combustion method featuring a change in magnetic properties as a function of composition. Wirunchit and Koetniyom (pssa.202200364) have employed hydrothermal process to prepare ZnO nanoparticles utilized as antibacterial materials with enhanced efficacy. Kansaard et al. (pssa.202200447) have presented the sonochemical synthesis of a composite compound and proposed it as a photocatalyst. Meejitpaisan et al. (pssa.202200441) have investigated photo- and X-ray-induced luminescence properties of Sm-doped oxyfluoroborate glasses as potential red-emitting laser medium and scintillators. Nayak et al. (pssa.202200651) have investigated sub-stochiometric nickel oxide films acting as hole selective contacts in silicon heterojunction solar cells and found that the performance of the device could be limited by the high interface defect density. Huang et al. (pssa.202200448) have reviewed the status and the challenges for the cast-mono silicon substrate technology as cost-effective wafers for solar cells. Yu and Rimjaem (pssa.202200263) have developed mid-infrared free-electron laser and terahertz emission generated by a corresponding electron accelerator. The ICREM organization with a history of already four past conferences and the 5th conference forthcoming in December 2023 (https://www.icrem2023.com/) has emerged as a prominent addition to the conference events in the community. In particular, it assists to establish cross-disciplinary links and collaborations across the boarders within the field of the radiation and emission in materials. We trust this physica status solidi (a) Special Issue comprising the highlights of the ICREM2022 can be of use for a wide and cross-disciplinary research community dealing with radiation effects, as well as for the students in the field to use the papers collected herein for studies, referencing, and inspirations. We thank all the authors and co-authors of the papers submitted to this Special Issue, as well as all participants of the ICREM2022 for attending the conference. With a great pleasure, we acknowledge the support provided to the ICREM2022 by the King Mongkut's Institute of Technology Ladkrabang as well as by all other sponsors. We also appreciate the networking opportunities partly enabled through the INTPART and UTFORSK Programs at the Research Council of Norway and the Directorate for Higher Education and Skills in Norway (NEARTEMS Project No. 322382 and SPECTRINKO Project No. UTF-2021/10210). Andrej Kuznetsov was awarded with his Ph.D. degree in physics from the Russian Academy of Sciences in 1992 and accomplished his habilitation in solid state electronics in 2000 at the Royal Institute of Technology in Sweden. In 2001 he joined the Department of Physics at the University of Oslo (UiO) in Norway as an associate professor, where he was subsequently promoted to a full professor rank in 2003. From 2018 he acts as the Chair of the UiO Centre of Excellence: Light and Electricity from Novel Semiconductors (LENS)—as a part of the Centre for Materials Science and Nanotechnology at UiO. He is an expert in the field of modern semiconductors, in particular focusing on the physics of diffusion, defects, and radiation effects. Wisanu Pecharapa received his B.S. in physics from Chiangmai University in 1992, M.S in physics from University of Central Florida, USA in 1997, and Ph.D. in physics from King Mongkut's Institute of Technology Ladkrabang (KMITL) in 2007. Currently, he is a professor at the College of Materials Innovation and Technology, KMITL. His research focus is on synthesis processes of metal oxide-based materials and composites, especially in low-dimensional structures that can be applied for optical, optoelectronics, and catalyst applications.
Keywords: Scope (computer science); Globe; Ion-surface interactions and analysis